(untitled) (Journal of the College of Basic Education, 2022)
The natural structure of the Islamic society differs from other societies in terms of the values ​​and concepts on which this society is based, as Islam was able, thanks to the systems and legislation it contains, to organize society and its sectors. Society, and as it is known, the Arab-Islamic society consisted of the following categories: Arabs, loyalists, dhimmis, and slaves ().The Arab, Islamic and non-Arabic sources and references have discussed these classes at length, but we will focus on the slave class that occupies the bottom of Islamic society, for the purpose of shedding light on this class that played thanks to Islam and its tolerant teachings.